PENINGKATAN PEMAHAMAN HUKUM MELALUI SOSIALISASI PENDAFTARAN NANAS BIKANG DI KABUPATEN BANGKA SELATAN SEBAGAI INDIKASI GEOGRAFIS - Darwance; Rafiqa Sari; Muhammad Syaiful Anwar (Prosiding Seminar Nasional Pengabdian Kepada Masyarakat, 2021)
Abstract Data from the Directorate General of Intellectual Property at the Ministry of Law and Human Rights of the Republic of Indonesia, Lada Putih Muntok (Muntok White Pepper) is the only registered geographical indication of the Bangka Belitung Islands. In fact, when referring to the scope of protection and the potential possessed based on that scope, there are still many other products that have the potential to be registered as geographical indications, one of which is the Bikang Pineapple in Bikang Village, Toboali District, South Bangka Regency. In accordance with the provisions of Article 53 of the Law of the Republic of Indonesia Number 20 of 2016 concerning Marks and Geographical Indications, in addition to the provincial or district/city regional governments, applications may be submitted by institutions representing the people in certain geographical areas who cultivate an item and/or product in the form of a source. natural resources, handicrafts, or industrial products, one of which is the Geographical Indication Protection Society (MPIG). Interactive socialization, starting with a pre-test, condensing material, discussion, and ending with a post-test, is a method that can solve the problem of not registering Bikang pineapple as a geographical indication. From the results of the activities carried out, it was found that people who initially did not understand the legal protection of geographical indications, after the socialization were carried out, became more understanding. Abstrak Data di Direktorat Jenderal Kekayaan Intelektual Kementerian Hukum dan HAM RI, Lada Putih Muntok (Muntok White Pepper) merupakan satu-satunya indikasi geografi terdaftar dari Kepulauan Bangka Belitung. Padahal, bila merujuk pada ruang lingkup perlindungan serta potensi yang dimiliki berdasarkan ruang lingkup itu, masih banyak produk lain yang berpotensi untuk didaftarkan sebagai indikasi geografis, salah satunya Nanas Bikang yang ada di Desa Bikang, Kecamatan Toboali, Kabupaten Bangka Selatan. Sesuai ketentuan Pasal 53 Undang-Undang Republik Indonesia Nomor 20 Tahun 2016 tentang Merek dan Indikasi Geografis, selain pemerintah daerah provinsi atau kabupaten/ kota, permohonan dapat diajukan oleh lembaga yang mewakili masyarakat di kawasan geografis tertentu yang mengusahakan suatu barang dan/atau produk berupa sumber daya alam, barang kerajinan tangan, atau hasil industri, salah satunya masyarakat perlindungan indikasi geografis (MPIG). Sosialisasi yang dilakukan secara interaktif, diawali pre test, pemapatan materi, diskusi, dan diakhiri dengan post test, merupakan metode yang dapat memecahkan masalah belum didaftarkannya nanas Bikang sebagai indikasi geografis. Dari hasil kegiatan yang dilakukan, didapati hasil masyarakat yang semula kurang memahami tentang perlindungan hukum terhadap indikasi geografis, setelah dilakukannya sosialiasi menjadi lebih memahami.